ChemInform Abstract: Concise Synthesis of Prenylated and Geranylated Chalcone Natural Products by Regiospecific Iodination and Suzuki Coupling Reactions. Issue 27 (8th July 2014) - Wang, Haomeng; Yan, Zhihong; Lei, Yanan; Sheng, Kai; Yao, Qingwei; Lu, Kui; Yu, Peng
Abstract Based on the regioselective iodination of the bis Mom‐protected methyl aryl ketones (I) a convenient synthesis of bavachalcone (VIIa) and isoxanthoangelol (VIIb) is developed.